Fuel briquettes – making business sense - Asamoah, B.; Nikiema, Josiane; Gebrezgabher, Solomie A.; Odonkor, E.; Njenga, M. (2017)
In recent years, interest in fuel briquetting increased because of the opportunity to utilise agricultural residues and the organic fractions of municipal solid waste for energy, with a potential reduction in environmental pollution levels, and where modern heating and cooking fuels for domestic, institutional, commercial and industrial use are not readily available or affordable.